Construction of the Meaning of a Motorcycle taxi Driver in Student Perception - Mubarok Mubarok; Urip Mulyadi (Journal of Advanced Multidisciplinary Research, 2020)
The development of technology gave birth to a new profession. Millennials plunge into online motorcycle taxi drivers. The presence of various online transportation applications such as Go-Jek, Grab, Uber opens wide opportunities to become partners. Millennials are not ashamed but feel proud. The motorcycle taxi profession which is often underestimated is now in demand by various groups. This study aims to explain the changes in the construction of the meaning of motorcycle taxi drivers in the perception of students who become online motorcycle taxi drivers. The change in meaning construction has made the online motorcycle taxi profession attractive to the younger generation. Changes in construction will be described in various stages of the scheme, the process of externalization, objectification and internalization of values. This research strategy is phenomenological research. The basic question according to Patton (2002) is to find out the essence of experience. Littlejohn (1999: 199) defines phenomenology as the study of experiences that come from consciousness or the way we understand something by consciously experiencing something. Hegel (in Moustakas 1994: 26) states that phenomenology refers to experience as arises from consciousness, he further explains phenomenology is the science of describing what a person receives, feels and knows in his direct awareness and experience. What arises from consciousness is what is called a phenomenon. With this strategy, the researcher seeks to obtain a systematic, logical and coherent reflection of the reality phenomenon about the motorcycle taxi profession